The Great Wall : [the extraordinary story of China's wonder of the world] - Man, John, 1941- (Cambridge, Mass. : Da Capo Press, 2008)
John Man travels the entire length of the Great Wall and across two millennia to find the truth behind the legends. Along the way, he delves into the remarkable and complex history of China--from the country's tribal past, through the war with the Mongols, right up to the modern day when the Great Wall is once more a commanding emblem of China, the resurgent superpower.
Subtitle from jacket.
Includes bibliographical references and index.
Keywords: Man, John, -- 1941- -- Travel; Great Wall of China (China) -- History; China -- History